Dose-dependent effectiveness of acellular pertussis vaccine in infants: A population-based case-control study. Issue 6 (5th February 2020) - Mack, I.; Erlanger, T.E.; Lang, P.; Sinniger, P.; Perisa, D.; Heininger, U.
Highlights: Acellular pertussis vaccines continue to offer effectiveness against hospitalization. Vaccine effectiveness is increasing from dose to dose. Timely immunization of infants is critical for optimal protection. Failure to vaccinate is a greater problem than vaccine failure. Abstract: Background: Pertussis is a vaccine-preventable disease which is most severe in young infants. More than two decades after the introduction of acelluar pertussis vaccines (aPV) in national immunization programs in many countries worldwide, a resurgence of pertussis has been recognized. Suboptimal effectiveness of aPV has been blamed as one major reason but only few studies have evaluated dose-dependent vaccine effectiveness (VE) provided by aPV in current practice. Methods: We performed a population-based retrospective case-control study by comparing pertussis immunization data of children 2.5 months to 2 years of age hospitalized for pertussis and residing in Switzerland with immunization data of a random control sample of children aged 2 years and residing in Switzerland. VE was defined as the percentage of hospitalizations avoided by number of aPV doses. It was calculated as 1-infection rate ratio (IRR)*100. IRR was calculated by dividing infection rates of vaccinated children and infection rates of unvaccinated children. To get dose specific VE,  infection rates were stratified by number doses received. Results: VE against hospitalization due to pertussis increased significantly with each consecutive aPV dose in a "3 + 1" primary course in infants: 42.1% (95% CI: 11.3–62.6), 83.9% (70.2–92.1), 98.2% (96.1–99.3), and 100% (97.9–100) after the 1st, 2nd, 3rd, and 4th dose, respectively. Conclusion: Acellular pertussis vaccines continue to demonstrate protection against hospitalization due to pertussis in infants and young children. Therefore, together with advancing immunization of pregnant women and household contacts, better control of severe pertussis in young infants can be achieved by timely initiation of immunization.